Sexual violence against Jewish women during the Holocaust - Hedgepeth, Sonja M. (Sonja Maria), 1952-; Saidel, Rochelle G. (HBI series on Jewish women., 2010)
The first book in English to specifically address the sexual violation of Jewish women during the Holocaust.